The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Anais Do Workshop De Computação Aplicada À Gestão Do Meio Ambiente E Recursos Naturais (WCAMA 2020) 2020
DOI: 10.5753/wcama.2020.11025
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Simulator for Green Smart Campus Systems

Abstract: The 2030 Agenda for Sustainable Development aims to foster environmental protection, inclusive economic growth, and social inclusion. Universities are called to join this global effort and are expected not only to contribute with solutions for the sustainability challenges but also provide sustainable campi. Given this scenario, the main contributions of this paper are threefold: i) to illustrate how universities could contribute with the 2030 Agenda through smart campus solutions based on technologies such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Higher Educational Institutes (HEIs) are mentioned specifically under the fourth SDG, which ensures inclusive and equitable quality education while also promoting lifelong learning opportunities for all. HEIs could also contribute to the remaining SDGs through teaching, research output as well as campus initiatives, such as implementing green smart campus solutions (Moraes et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher Educational Institutes (HEIs) are mentioned specifically under the fourth SDG, which ensures inclusive and equitable quality education while also promoting lifelong learning opportunities for all. HEIs could also contribute to the remaining SDGs through teaching, research output as well as campus initiatives, such as implementing green smart campus solutions (Moraes et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This responsibility of the university will be achieved by making concerted efforts directly and indirectly and paying adequate attention to protecting the environment, social inclusion and comprehensive economic growth. One of the many ways universities can add value to sustainable development goals is to establish smart campus solutions (Moraes et al, 2020). Studies have shown that smart campus solutions provide technologies for achieving the following SDGs: clean water and sanitation (Kuo et al, 2018), affordable and clean energy (Weng et al, 2019;Yuliansyah et al, 2019), sustainable cities and communities (Liu et al, 2017;Subbarao et al, 2019), responsible consumption and production (Lo, 2019) and climate action (Liu et al, 2017;Rodrigues et al, 2019).…”
Section: Introductionmentioning
confidence: 99%